2008
DOI: 10.1111/j.1471-0307.2008.00408.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microencapsulation on Viability of Lactobacillus acidophilus LA‐5 and Bifidobacterium bifidum BB‐12 During Kasar Cheese Ripening

Abstract: The viability of encapsulated Lactobacillus acidophilus LA‐5 and Bifidobacterium bifidum BB‐12 by emulsion or extrusion techniques in Kasar cheese was investigated. The microbiological, biochemical and organoleptic properties of cheeses were assessed throughout 90‐day storage. Results showed that the viability of probiotic bacteria was maintained to a great extent by microencapsulation. No difference was noted between the two encapsulation techniques with regard to bacterial counts, proteolysis and organolepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(26 citation statements)
references
References 25 publications
3
21
0
2
Order By: Relevance
“…Özer et al . () and Gonzalez‐Sanchez et al . () concluded that encapsulation can be a good way to enhance probiotic viability in Kasar cheese and Kefir cheese respectively.…”
Section: Application Of Encapsulated Probiotics In Food Areamentioning
confidence: 91%
“…Özer et al . () and Gonzalez‐Sanchez et al . () concluded that encapsulation can be a good way to enhance probiotic viability in Kasar cheese and Kefir cheese respectively.…”
Section: Application Of Encapsulated Probiotics In Food Areamentioning
confidence: 91%
“…As mentioned previously, cheese is considered a suitable delivery for probiotics to the human intestine compared to the fermented milks because of the chemical composition and physical properties of cheese (e.g., high pH, low acidity, high fat content, high buffering ability, low oxygen, and the dense matrix or thickness of cheese texture) that could increase the viability of probiotic microorganisms. Probiotic bacteria have been used in manufacturing different varieties of cheese around the world, namely Ras or Roumy cheese [7], Mascarpone cheese [28], Minas fresh cheese [29,30], fresh cheese [31], soft cheese [32], fresh cream cheese with inulin as supplement [33], Festivo cheese [19], Crescenza cheese [20], Fresco cheese [9], cottage cheese [15], Petit-Suisse cheese [34], Pategrás cheese [35,36], Tallaga cheese [37], Iranian-type white cheese [38], Karish cheese [14], Cremoso cheese [36], Gouda cheese [16], probiotic goat's cheese [39,40], Canestrato Pugliese hard cheese [3], Turkish white cheese [10], Cheddar cheese [13,26,41,42], Turkish-type Beyaz cheese [43], white-brined cheese [44], Kasar cheese [45], and cheese dips [46]. It has been reported that many probiotics (such as B. animalis ssp.…”
Section: Cheese As Probiotic Food Matrixmentioning
confidence: 99%
“…Microencapsulation is a promising technique for bacterial cell protection and several studies have been carried out investigating the protective role of this technique against adverse conditions to which probiotics can be exposed (Capela et al, 2006;Chen et al, 2006;Heidebach et al, 2010;Mandal et al, 2006;Michida et al, 2006;Özer et al, 2008;Sheu and Marshall, 1993;Sultana et al, 2000). One advantage of microencapsulation with hydrocolloids is that cells are entrapped within the matrix during the formation of the spheres, while in other techniques such as spray drying, freeze drying and fluidized bed drying, the microorganisms are completely released into the product (Krasaekoopt et al, 2003).…”
Section: Introductionmentioning
confidence: 99%